Education to Work Transition: An Interpretive Inquiry of Status and Struggle of Pahari Youth - Pahadee, Babita (Nepal Journal of Multidisciplinary Research, 2023)
Education to work transition is the phase encountered by youths while moving to labor market in search of job. This study was conducted to examine how Pahari youths in Badikhel's Godawari Municipality-4 transition from higher secondary education to employment using a qualitative interpretative inquiry as a research paradigm. The research explored the experiences of Pahari youth who dealt with evolving circumstances, beliefs, and perceptions over the time transitioning from school to work. The theoretical bases of the study are Social Cognitive Career Theory, Capability Approach, and Schlossberg's transition theory. Following the theoretical sampling method, 5 participants were selected purposively as a sample for the study. Two males and three females were chosen by applying the purposive sampling method. In-depth semi-structured interviews were conducted and categorized themes into three categories; social and economic situation, the importance of support in a transition period, and uneven transition of Pahari youth. The study found that Pahari youths are struggling to pursue higher education due to financial problems, family issue, social pressure and the like. Because of this, transitioning Pahari youths from education to work is very challenging. They cannot complete their education, which limits the skills related to the professional sector. As a result, getting engaged, even in a small part-time job with few wages, has become essential to sustain their lives and their families. Despite this, Pahari youths are found aware of these challenges and trying to overcome the situation. This study suggests the government prioritize the Pahari community for education, which could benefit Pahari youths to get the higher qualification and find better employment opportunities in the long term.